PLASMID FINGERPRINTING AND VIRULENCE GENE DETECTION AMONG INDIGENOUS STRAINS OF SALMONELLA ENTERICA SEROVAR ENTERITIDIS - Sajid, Saraj Uddin; Schwarz, Stefan (Journal of Ayub Medical College Abbottabad, 2009)
Background: Salmonella enterica serovar Enteritidis is an important frequently reported zoonotic pathogen and a common cause of human gastroenteritis worldwide. The highly conserved Serospecific plasmids (SSPs) and Salmonella plasmid virulence (Spv) genes have been shown to mediate extra-intestinal colonization and systemic infection. The objective of current study was to document the presence of SSPs and SpvB/SpvC genes prevailing in the indigenous population of serovar Enteritidis. Methods: A total of 48 epidemiologically unrelated strains of Salmonella enteritidis were included in the study. Preparation of plasmids DNA suitable for endonuclease digestion and separation of respective fragments by agarose gel electrophoresis followed previously described protocols. The plasmids of Escherichia coli V517, 1-kbp ladder, and Î» DNA HindIII fragments served as DNA size standards. Transfer of DNA fragments from agarose gels to nitrocellulose membranes was achieved by capillary blot procedure. An ECL labeled 3.6 kbp HindIII fragment of plasmid PRQ 51 was used as probe for SpvB/SpvC gene detection. Results: Plasmid DNA fingerprinting revealed the presence of two different profiles of approximately 55 kbp and 90 kbp and were identified as virulence plasmids by DNA hybridization. The SpvB/SpvC genes were located on HindIII fragments of 3.6 kbp in each of the two types of virulence plasmids. Conclusion: The study confirms the presence of SSPs and SpvB/SpvC genes in indigenous strains of S. enteritidis isolated from Northern Punjab area of Pakistan and substantiate the previous data on such findings from other parts of the world. Keywords: Salmonella enteritidis; virulence plasmids, SpvB/SpvC genes